SOME PROBLEMS AND MAIN ORIENTATING POINTS OF STRATIGRAPHY IN THE EARLY XXI CENTURY - Gladenkov Yu.B. (My University, 2004)
Principal trends in development of present-day stratigraphy are analyzed. Most important orientating points of stratigraphy in upgrading the global stratigraphic scale and interpreting geological processes are discussed.